An Investigation of Changing Attitudes and Behaviors and Problematic Internet Use in Children Aged 8 to 17 Years During the COVID-19 Pandemic. (February 2022) - Kamaşak, Tülay; Topbaş, Murat; Ozen, Nalan; Esenülkü, Gülnur; Yıldız, Nihal; Şahin, Sevim; Acar Arslan, Elif; Çil, Elif; Kart, Pınar Özkan; Cansu, Ali
Purpose: To examine the effects of the COVID-19 pandemic on the lifestyle, habits, and behavioral differences in children, and their changing internet use habits. Methods: The research was planned as a cross-sectional study involving 4892 children aged 8 to 17 years attending schools in the city center of Trabzon, Turkey. Children's daily living activities, social habits, mood and temperament changes, and internet use were investigated before and during the pandemic. In terms of problematic internet use, internet addiction rates were evaluated using the validated Turkish-language version of the Parent-Child Internet Addiction Scale (PCIAT-20). Results: The children's mean age was 13 ± 2.45 years, and 17.1% (n = 837) exhibited problematic internet use features on the PCIAT-20. Problematic internet use was higher in boys and in children older than 13 years. The presence of COVID-19 infection among members of the household, quarantine measures, attending private schools, the mother's occupation, the time spent by the mother and father on their mobile phones, and high parental education levels were associated with a high level of internet addiction. Families also described significant changes in their children's temperament and character compared with the pre-pandemic period. Conclusion: The prevalence of problematic internet use increased during the COVID-19 pandemic compared with previous studies from Turkey. Children were also more introverted, irritable, and pessimistic during the pandemic.